Relationship between social support and parenting sense of competence in puerperal women: Multiple mediators of resilience and postpartum depression - Shang, Xingchen; Li, Lin; Niu, Changmin; Liao, Yuexia; Gao, Shuang (Frontiers in Psychiatry, 2022)
Background: Maternal role competence is an important marker of achievement in the role of the mother, but parenting sense of competence (PSOC) among puerperal women is not high. Psychosocial factors, particularly social support, postnatal depression and resilience, have been identified as significant predictors of maternal role competence. However, information is limited regarding the mechanisms through which these psychosocial factors affect maternal role competence. Objective: To evaluate the multiple mediators of resilience and postpartum depression (PPD) in the relationship between social support and PSOC in puerperal women. Methods: A cross-sectional study was performed in a tertiary general hospital in Yangzhou, China. A total of 234 puerperal women at 6–8 weeks after birth completed the socio-demographic questionnaires, Social Support Rating Scale, Connor–Davidson Resilience Scale, Edinburgh Postnatal Depression Scale, and PSOC Scale. Results: Resilience and PPD mediated the relationship between social support and PSOC. The mediation effect of resilience and PPD and the total mediation effect were significant, individually accounting for 22.96%, 21.70%, and 44.65%, respectively, of the total effect. Moreover, pairwise contrast between the two indirect effects was not significant. The difference between the two pathways suggests that resilience and PPD play different roles in the relationship between social support and PSOC. Conclusions: This study showed that social support may exert its effects on PSOC in puerperal women with multiple mediators of resilience and PPD. This therefore highlights potential intervention targets to improve PSOC.